The Effect of Video-Based Learning Media on Social Studies Learning Outcomes - Vivit Sriwatie; Raras Gistha Rosardi; Moh Irsyad Fahmi MR; Agustina Tri Wijayanti; Saliman (Universitas Negeri Yogyakarta, 2026)
This study was motivated by the low Social Studies learning outcomes of Grade IX students at SMPN X di Gunung Bintang Awai, where 40% of students failed to meet the minimum mastery criteria (KKM) due to monotonous, lecture-dominated teaching methods. This study aimed to examine the effect of video-based learning media, integrated with structured discussion and interactive quizzes, on students’ Social Studies learning outcomes. A pre-experimental one-group pretest-posttest design was employed, involving 28 students (12 male, 16 female) selected through total sampling. The intervention was implemented over five months (March–July 2025) and combined video-based instructional media with structured group discussions using guided worksheets (Lembar Kerja Peserta Didik) and interactive gamified quizzes. Learning outcomes were measured using a cognitive achievement test administered before (pretest) and after (posttest) the intervention. Data were analyzed using a chi-square test of association to examine the difference in classical completeness proportions between the two measurements. Results showed that the proportion of students achieving learning completeness increased significantly from 35.7% at pretest to 92.8% at posttest, χ²(1) = 17.50, p < .001, with a large effect size (φ = 0.60). These findings indicate that video-based learning media, when embedded within an active pedagogical design, significantly improves cognitive learning outcomes. However, because instructional components were introduced progressively within a single group and no control group was included, causal attribution to video media in isolation should be interpreted with caution. Further quasi-experimental research incorporating a control group is recommended to confirm these findings.